Laughing alone, together: local user-generated satirical responses to a global event. Issue 7 (19th May 2022) - Nissenbaum, Asaf; Shifman, Limor
ABSTRACT: This paper presents a first systematic analysis and conceptualization of local comic responses to global events, as articulated by internet users. We probed the multifaceted interactions between the global-local and entertaining-disruptive dimensions of contemporary satire through a cross-linguistic analysis of reactions to Donald Trumps' election. Using a combination of qualitative methods, we analyzed humorous messages in Arabic, Chinese, English, German, and Spanish ( n = 321) on Twitter and Weibo during November 2016. We found that globally shared themes are mainly apolitical and entertaining, while glocal responses align with three ideal types, which we term inbound, transitional, and outbound satire. Each type of satire featured a distinct combination of protagonists, targets and humor mechanisms. In conclusion, we discuss how cross-national satire on social media problematizes the (already murky) distinction between entertaining and disruptive satire, why satire is uniquely equipped to domesticate global affairs through estrangement, and how our typology may be linked to bilateral relations between countries in the contemporary international arena.